Clinical handover experience among nurses working in Ethiopia: phenomenological qualitative study - Gurmu Dumbala; Yeshitila Belay; Ebrahim Yimam; Yonas Abebe (BMC Nursing)
Abstract Background A nurse’s clinical handover is an important and complex form of communication in healthcare organizations that involves the exchange of patient-related information during shift change. Nurse-to-nurse clinical handover is frequently implemented at inpatient and emergency units, with an increased risk of information loss. Ineffective clinical handover is responsible for about 80% of the causes of serious, preventable adverse health events. However, the evidence is unknown in Ethiopia, particularly in the study setting. Therefore, this study aimed to explore the lived experience of clinical handover among nurses working in the Jimma Medical Center in South Western Ethiopia in 2022. Method This study employed a descriptive phenomenological approach to explore the lived experiences of nurses in medical, surgical, and emergency outpatient departments. Data collection occurred between July 1st and August 31st, 2022. Nine nurses, purposively selected for their diverse experiences, participated in individual, semi-structured, in-depth interviews. To provide additional context, five key informants were also interviewed. Additionally, twenty non-participatory observations were conducted. Interview recordings and field notes were transcribed verbatim and analyzed using Colaizzi’s seven-step method, facilitated by Atlas.ti 8 software. Rigor was ensured through adherence to Lincoln and Guba’s criteria for trustworthiness. Findings are presented through thematic narratives supported by direct participant quotations. Result Analysis of the data revealed three emerged core themes of the clinical handover experience: i) “Inconsistent, non-standardized handover processes and content”- with subthemes:“communication styles”,“location of handover”,“time of handover”, “the content of handover”,“patient involvement”, and“handover responsibility.” ii) “Obstacles to consistent handover”, with subthemes such as” healthcare system-related factors”, “care provider-related factors”, and “patient’s health status-related factors”. iii) “Negative impacts on patients from inconsistency in handover.” All participants reported that ineffective clinical handover was harming the holistic quality of nursing care. Conclusion This study found that consistent and standardized clinical handover practice has a significant deficit, which was affected by obstacles related to nurses, the organizational healthcare system and the patient’s health status. Therefore, tailored intervention is needed to improve the clinical handover in nursing practice.